The veiled one eaudiobook Inspector wexford mysteries series, book 14. - Rendell, Ruth (Chief Inspector Wexford Mystery, 2018)
Who would garrote a middle-aged housewife and leave her body in the parking garage of a suburban shopping mall? Chief Inspector Wexford is no sooner on the case than a car bomb's explosion lands him in the hospital. It's now up to Mike Burden to step in and solve the case. He's got a suspect . . . but will he be able to make him talk?